2017
DOI: 10.1016/j.vaccine.2016.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and protective efficacy of a single-dose live non-pathogenic Escherichia coli oral vaccine against F4-positive enterotoxigenic Escherichia coli challenge in pigs

Abstract: Enterotoxigenic Escherichia coli strains expressing F4 (K88) fimbriae (F4-ETEC) are one of the most important causes of post-weaning diarrhea (PWD) in pigs. F4, a major antigen, plays an important role in the early steps of the infection. Herein, the efficacy of a live oral vaccine consisting of a non-pathogenic E. coli strain expressing F4 for protection of pigs against PWD was evaluated. Three blinded, placebo-controlled, block design, parallel-group confirmatory experiments were conducted, using an F4-ETEC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 28 publications
4
56
0
1
Order By: Relevance
“…This can stimulate the intestinal colonization by these E. coli which induces the secretion of intestinal antibodies, and finally blocks the adherence of ETEC. A wide range of on-farm studies have shown a reduced mortality and reduced use of antibiotics after oral administration of a live attenuated or live non-enterotoxigenic F4 + E. coli strain to pigs immediately after weaning ( Fuentes et al., 2004 , Ruan and Zhang, 2013 , Fairbrother et al., 2016 ).…”
Section: Applications Of Preventing Postweaning Diarrhea Associated Wmentioning
confidence: 99%
“…This can stimulate the intestinal colonization by these E. coli which induces the secretion of intestinal antibodies, and finally blocks the adherence of ETEC. A wide range of on-farm studies have shown a reduced mortality and reduced use of antibiotics after oral administration of a live attenuated or live non-enterotoxigenic F4 + E. coli strain to pigs immediately after weaning ( Fuentes et al., 2004 , Ruan and Zhang, 2013 , Fairbrother et al., 2016 ).…”
Section: Applications Of Preventing Postweaning Diarrhea Associated Wmentioning
confidence: 99%
“…[ 61 , 62 ]. Coliprotec ® F4 (Prevtec Microbia GmbH, Montrela, Canada) [ 63 ] and the recently reported oral bivalent F4/F18 vaccine [ 64 ] are attenuated vaccines designed for the active immunization of pigs against PWD, but there are no data available on their effect in sows.…”
Section: Different Types Of Vaccinesmentioning
confidence: 99%
“…2A, B). (Table 3) and IPEC-J2 (Table 4) (20,21,41,43). Furthermore, in contrast to other fimbriae, the adhesive subunit of F18 fimbriae is its minor subunit, thus purified F18 fimbriae is unable to induce anti-F18 antibodies and provide protection from PWD caused by F18+ ETEC strains (22).…”
Section: Mouse Serum Antibody Adherence Inhibition Assaymentioning
confidence: 99%
“…Vaccination with either purified fimbriae or adhesive subunits of fimbriae are reported to be efficacious in protecting and controlling piglet PWD (15)(16)(17)(18)(19). Currently, Fairbrother et al demonstrated that weaned piglets oral vaccinated with a single-dose live monovalent F4 vaccine (Coliprote ○ R F4, Prevtec Microbia) can protect immunized piglets against a F4+ ETEC challenge at 3, 7 or 21 days (20). Further, Nadeau et al demonstrated that weaned piglets administrated with a single oral dose of a bivalent F4/F18 vaccine (Coliprote ○ R F4/F18, Prevtec Microbia) can protect immunized piglets challenged with both F4+ and F18+ ETEC (21).…”
Section: Introductionmentioning
confidence: 99%